Digital-Forensics and Watermarking 14th International Workshop, IWDW 2015, Tokyo, Japan, October 7-10, 2015, Revised Selected Papers - Shi, Yun-Qing; Kim, Hyoung Joong; Pérez-González, Fernando; Echizen, Isao (Security and Cryptology, 2016)
This book constitutes revised selected papers from the 14th International Workshop on Digital-Forensics and Watermarking, IWDW 2015, held in Tokyo, Japan, in October 2015. The 35 papers presented in this volume were carefully reviewed and selected from 54 submissions. The contributions are organized in topical sections named: digital forensics; steganography and steganalysis; digital watermarking; reversible data hiding; and visual cryptography.